Proposta de gerenciamento com logística reversa de medicamentos para Araguaína Tocantins - Arantes, Fernando de Souza (2023)
The city of Araguaína located in the state of Tocantins faces challenges regarding low adherence to reverse medication logistics. A survey carried out in 2022 revealed that only 32% of the 59 pharmacies or drugstores in the aforementioned city accept medicines for proper disposal. The objective of this work is to develop a proposal for reverse logistics of medicines for the municipality of Araguaína – TO. The proposal uses a scheduling platform to facilitate the collection of medicines to be donated. The research adopted a multifaceted approach, integrating methods such as a systematic literature review using MethodiOrdinatio, online opinion research and interviews with a pharmacist and a hospital manager who previously served as health secretary in a neighboring municipality. The systematic review analyzed 17 articles from different databases, including Scielo, Science Direct, Scopus and Web of Science, identifying problems and solutions in similar contexts. The online opinion survey had the participation of 398 people, revealing that 91.45% would be willing to donate unexpired and unused medicines. When asked about the reuse of these medicines in the public health system, 90.20% were in favor. After the interview with health professionals, it was possible to define a flow that goes from scheduling collection to making medicines suitable for donation by the Unified Health System (SUS) available for reuse. This includes the delivery of expired or disused medicines, undergoing screening/evaluation carried out by pharmacists working in municipal health units. Furthermore, a system was developed that allows collections to be scheduled, appointment management and stock management, including donations and withdrawals, after due screening/evaluation. These measures aim to create a comprehensive and effective solution to improve the reverse logistics of medicines in Araguaína - TO.